Mengenalpasti fenotip apolipoprorein E dengan menggunakan teknik fokus isoelektrik bagi kes-kes hiperlipidemia di Kelantan - Rashid, Faridah Abdul; Mansur, Mazidah Ahmad; Nordin, Hasenan (1999)
Patients plasma samples (n=250) were screened for cholesterol and triglyceride content by enzymatic analyses performed on an automated chemistry analyzer using standard kits. Lipoprotein electrophoresis was performed on thin slab or pre-casted tube gels.Unrelated plasma were selected (n=24) and studied using both gel methods. One subject with a possible apolipoprotein E-2/2 phenotype was detected by the slab gel method. Another 11 subjects with unusual lipoprotein banding patterns and possible altered apolipoprotein E phenotypes were detected by the tube gel method. VLDL were isolated by a micromethod developed on an ultracentrifuge. Apolipoprotein E phenotype was confirmed by flat bed isoelectrtc focussing (IEF) of delipidated VLDL proteins on commercial and homemade IEF gels.